The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsami.5b02662
|View full text |Cite
|
Sign up to set email alerts
|

3D Scaffolds with Different Stiffness but the Same Microstructure for Bone Tissue Engineering

Abstract: A growing body of evidence has shown that extracellular matrix (ECM) stiffness can modulate stem cell adhesion, proliferation, migration, differentiation, and signaling. Stem cells can feel and respond sensitively to the mechanical microenvironment of the ECM. However, most studies have focused on classical two-dimensional (2D) or quasi-three-dimensional environments, which cannot represent the real situation in vivo. Furthermore, most of the current methods used to generate different mechanical properties inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 41 publications
2
159
0
Order By: Relevance
“…Decellularized bone can avoid this mismatch and has natural porous microstructure and 3D interconnectivity, which are beneficial to migration and infiltration of endogenous stem cells. In our previous study 15 , novel 3D scaffolds with different matrix elastic modulus (6.74 ± 1.16 kPa, 8.82 ± 2.12 kPa, and 23.61 ± 8.06 kPa) but same microstructure have been successfully fabricated by coating decellularized bone with collagen (Col)/hydroxyapatite (HA) mixture in different collagen ratios. Our study has proved that the scaffold with optimal matrix elastic modulus (23.61 ± 8.06 kPa) can promote the osteogenic differentiation of MSCs in vitro and enhance the new bone formation in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Decellularized bone can avoid this mismatch and has natural porous microstructure and 3D interconnectivity, which are beneficial to migration and infiltration of endogenous stem cells. In our previous study 15 , novel 3D scaffolds with different matrix elastic modulus (6.74 ± 1.16 kPa, 8.82 ± 2.12 kPa, and 23.61 ± 8.06 kPa) but same microstructure have been successfully fabricated by coating decellularized bone with collagen (Col)/hydroxyapatite (HA) mixture in different collagen ratios. Our study has proved that the scaffold with optimal matrix elastic modulus (23.61 ± 8.06 kPa) can promote the osteogenic differentiation of MSCs in vitro and enhance the new bone formation in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…An important parameter is the pore size. The average pore diameter of the decellularized cancellous bone is in a range of 389.3 ± 134.9 μm [92]. Several studies have shown that a pore size between 300 and 500 μM is necessary for the adhesion, differentiation and growth of osteoblasts [93,94].…”
Section: Co-cultures Of Osteoblasts and Osteoclastsmentioning
confidence: 99%
“…Although increased physical protection and the presence of an adherent substrate are likely at least partially responsible for the improved performance of scaffold-supported cellular transplants in this study, its findings indicate that maintaining the proper biomechanical context may be an important factor for successful cell- based therapy in the CNS. Indeed, other studies have demonstrated that the stiffness of 3D scaffolds can influence stem cell behavior [65, 66]. …”
Section: Engineered Materials For Improved Neural Tissue Engineeringmentioning
confidence: 99%